Meninos e meninas: uma análise dos estudos de peer effects com foco em composição de gênero - Andrade, Ricardo Elias Mauad de (2017)
The present work inspects the literature on peer effects and bring the main identification issues on the phenomenon. In particular, it analyzes papers that study the gender composition and the behavior answers for situations in which the composition is changed, mainly in educational environment, addressing works that make a distinction between mix and exclusive gender groups. It discusses the results of these papers, showing that a higher female share in peer groups has positive impacts - meaning higher grades and a more welcoming class environment sensed by students - although it cannot be said whether this effects are endogenous or exogenous.